For this case we have the following equation:
[tex]3 \sqrt{x+6}=-12 [/tex]
Rewriting we have:
[tex]\sqrt{x+6}= \frac{-12}{3} [/tex]
[tex]\sqrt{x+6}=-4[/tex]
We raise both members of the equation to the square:
[tex](\sqrt{x+6})^2=(-4)^2[/tex]
Rewriting we have:
[tex]x+6=16[/tex]
[tex]x=16-6[/tex]
[tex]x=10[/tex]
It's a extraneous solution because equality is not met by substituting x = 10 in the original equation:
[tex]3 \sqrt{10+6}=-12 [/tex]
[tex]3 \sqrt{16}=-12 [/tex]
[tex]3(4)=-12 [/tex]
[tex]12=-12 [/tex]
Answer:
The solution is:
[tex]x=10[/tex]
It's a extraneous solution